“NÃO VEJO A VIDA SEM TRABALHO”: repercussões do trabalho e do processo de aposentadoria na subjetividade de docentes de uma instituição federal de ensino superior - FREIRE, Fabiana Moreira Lima (2018)
It is understood that, work in capitalist society, acquires a central role and that, retirement appears as a significant moment of transition for those who are affected by it. The general objective was to analyze the repercussions of the work and the retirement process on the subjectivity of teachers of a Federal Institution of Higher Education, with right acquired for the retirement and who are receiving payment of permanence. The aim was to understand the meaning of work and retirement for the participants, as well as identify elements that generate pleasure and suffering in the daily work and identify aspects that prolong the permanence in activity. The theoreticalmethodological reference used was based on the conceptual approach of Work Psychodynamics and Historical Social Psychology, based on the reference of historical-dialectical materialism. Eight teachers were interviewed through a semi structured interview. To analyze the data, the Critical Discourse Analysis of Fairclough (2008) was used. It was verified the predominance of positive aspects related to the work, being this one identified as place of identification, source of recognition and achievement. It was observed that in spite of the difficulties found, in several situations, the participants of this study manage to mobilize themselves by the use of practical intelligence and cooperation, and develop their work activities in a satisfactory way, which suggests the predominance of experiences of pleasure. The possibility of retiring from work was assessed with concern about the decrease in the pace of life and doubts about how to complete and manage the time that was once exclusively devoted to work. Despite concern about possible financial losses arising from retirement, what determines their postponement, for most participants, is the achievement they achieve through work, commitment to the institution and the fear of interrupting a productive life. It was evidenced the importance of expanding spaces for debate and reflection on the theme, in order to highlight the need for preparation for the retirement process.